2008
DOI: 10.1038/sc.2008.75
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic paraplegia: care management characteristics within a rehabilitation center

Abstract: Study design: Retrospective study. Objectives: To determine the potential impact of rehabilitation care on associated symptoms and functional improvements of paraplegic patients with metastatic spinal cord compression. Setting: CMN Propara, Montpellier (France). Measures: Demographics, Functional Independence Measure (FIM), Frankel Modified Score and Visual Analog Scale (VAS) for pain, intercurrent adverse medical events and neurological outcome, duration of stay, survival time, rehospitalization in a non-Spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
1
15
1
2
Order By: Relevance
“…Similar conclusions have been made by other groups that examined the outcome of patients with metastatic spinal cord lesions. 12 In our patients, the need for early discharge was avoided because of the nature of their tumors; most patients had a prognosis of several months or longer, which allowed protracted rehabilitation stays.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar conclusions have been made by other groups that examined the outcome of patients with metastatic spinal cord lesions. 12 In our patients, the need for early discharge was avoided because of the nature of their tumors; most patients had a prognosis of several months or longer, which allowed protracted rehabilitation stays.…”
Section: Discussionmentioning
confidence: 93%
“…[2][3][4][5][6][7][8][9][10][11][12] Most such studies, however, examined metastatic spinal cord compression only, and although they have demonstrated the benefits of rehabilitation in neoplastic patients with regard to pain, independence, prevention of complications and survival, they failed to make comparisons with traumatic SCI (TSCI) patients. [5][6][7][9][10][11][12] Thus, few studies have compared the outcomes of NSCI and TSCI patients, likely because of differences in prognostic factors (age, lesion severity and level, and lesion-to-rehabilitation hospital admission time) between these groups that render them incomparable.…”
Section: Introductionmentioning
confidence: 99%
“…5,10,[12][13][14][15][16]25,26 The key findings from these are summarized in Table 1. A number of reports compared people with SCDys due to tumor to those with traumatic SCI and found that the tumor group had a shorter length of stay in SRU, comparable improvement in functional abilities and similar rates of discharge back into the community.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[7][8][9] The bias of SRUs against admitting people with SCDys appears to be particularly strong regarding those people with SCDys due to tumor, 10,11 although numerous SRUs do admit these patients. 5,10,[12][13][14][15][16][17] It is acknowledged that the rehabilitation of patients with tumor presents unique challenges, 18 and this applies especially for those with tumor as the cause of SCDys. 10,16,[19][20][21] Despite the high proportion of people with tumor causing SCDys there has been relatively little written about these patients in terms of the ideal setting for their rehabilitation or recommendations for rehabilitation teams caring for them.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with MSCC, even more difficult to quantify is the opportunity cost of rehabilitation in terms of time away from family members and loved ones in the context of finite survival. 14 Current research on rehabilitation following MSCC [15][16][17][18][19][20][21][22][23][24][25][26] is comprised of predominantly small retrospective chart reviews with sample sizes ranging from 26 24 to 108 25,26 patients, in a maximum of seven centers. 16 Though some of these studies have compared …”
mentioning
confidence: 99%